Immunodiagnosis of cysticercosis by ELISA in lambs infected with Cysticercus tenuicoilis - Panda, M R; Ghosh, S; Varma, T K (The Indian Journal of Animal Sciences, 2012)
An enzyme-linked immunosorbent assay was standardized for the diagnosis of Cysticercus tenuicollis infection in lambs experimentally infected with 3 000 eggs of Taenia hydatigena and naturally infected sheep. The sensitivity of whole cyst antigen in the sera of experimental lambs was 83% whereas with the sera from sheep harbouring natural C. tenuicollis infection was 84.6%. The positivity was 30 to 53.8% with Pâ‚ and Pâ‚‚ fractions. Of all the antigens tested the whole cyst antigen was most reactive and Sephadex G-100 fractionation method was found unsuitable for purification of the antigen.